Hand-assisted laparoscopic surgery versus conventional open surgery in intraoperative and postoperative outcomes for colorectal cancer: An updated systematic review and meta-analysis. Issue 33 (August 2017) - Zhang, Xubing; Wu, Qingbin; Gu, Chaoyang; Hu, Tao; Bi, Liang; Wang, Ziqiang
Abstract: Aim: This meta-analysis aims to compare hand-assisted laparoscopic surgery (HALS) and conventional open surgery (OS) for colorectal cancer (CRC) in terms of intraoperative and postoperative outcomes, and to explore the safety, feasibility of HALS for CRC surgery. Methods: A systematic literature search with no limits was performed in PubMed, Embase, and Medline. The last search was performed on April 23, 2017. The outcomes of interests included intraoperative outcomes (operative time, blood loss, length of incision, transfusion, and lymph nodes harvested), postoperative outcomes (length of hospital stay, length of postoperative hospital stay, time to first flatus, time to first liquid diet, time to first soft diet, time to first bowel movement, postoperative complications, reoperation, ileus, anastomotic leakage, wound infection, urinary complication, pulmonary infection, and mortality). Results: Fifteen articles published between 2007 and 2017 with a total of 1962 patients with CRC were included in our meta-analysis. HALS was associated with longer operative time, less blood loss, smaller length of incision, shorter hospital days and postoperative hospital days, less time to first flatus, less wound infection, and less postoperative complications. There was no difference in blood transfusion, lymph node harvested, time to first liquid or soft diet, time to first bowel movement, reoperation, ileus, anastomotic leakage, pulmonary infection, urinary complications, or mortality. Conclusions: Our meta-analysis suggests that HALS in CRC surgery improves cosmesis and results in better postoperative recovery outcomes by reducing postoperative complications and hospital days. Furthermore, a large randomized control study is warranted to compare the short-term and long-term outcomes of those 2 techniques for CRC treatment.